Снижение виброактивности зубчатых передач применением асимметричной функции передаточного отношения - Карпов, Алексей Петрович; Носко, Павел Леонидович; Филь, Павел Владимирович; Бойко, Григорий Алексеевич (НТУ "ХПИ", 2016)
Разработана математическая модель синтеза рациональных геометрических параметров зубчатых передач с асимметричной функцией передаточного отношения на основе предложенных основных и дополнительных условий синтеза. Проведена экспериментальная оценка передаточного отношения и резонансных колебаний зубчатых передач некруглыми колесами. На основании выполненных исследований сделано заключение о целесообразности применения зубчатых передач с асимметричной функцией передаточного отношения для борьбы с резонансными колебаниями, что позволяет расширить функциональные возможности применения передач некруглыми зубчатыми колесами.

A mathematical model to synthesize rational geometric parameters of gearing with an asymmetrical function of the gear ratio was developed based on proposed and auxiliary synthesis conditions. A theoretical analysis of the performance of the synthesized gearing by comparing them with the gears having a constant gear ratio. Spend estimate of the resonant vibration for gearing with non-circular gears and asymmetric function of the gear ratio of the excitation pulse. The dependences for determining the boundaries of zones of occurrence of resonant vibrations. Using non-circular gears was shown to be advantageous for preventing resonance oscillations. An experimental study of the gear ratio and resonance oscillations in a two-stage gearbox with non-circular gears was done. The experiments showed no increase in the vibration level in the gearbox. Gear transmissions with the asymmetrical function of the gear ratio were concluded to be efficient for preventing resonance oscillations. This allows extending the applicability of non-circular gear transmissions.
Reduction of gear transmission vibroactivity using an asymmetrical function of the gear ratio
Keywords: редуктор; некруглые зубчатые колеса; вибрация; резонансные колебания; синтез зацепления; gearbox; non-circular gears; resonance oscillations; gear mesh synthesis